Science, Medicine, and Aristocratic Lineage in Victorian Popular Fiction - Boucher, Abigail (Cham : Springer International Publishing : Imprint: Palgrave Macmillan, 2023)
Science, Medicine, and Aristocratic Lineage in Victorian Popular Fiction explores the dialogue between popular literature and medical and scientific discourse in terms of how they represent the highly visible an pathologized British aristocratic body. This books explores and complicates the two major portrayals of aristocrats in nineteenth-century literature: that of the medicalised, frail, debauched, and diseased aristocrat, and that of the heroic, active, beautiful 'noble', both of which are frequent and resonant in popular fiction of the long nineteenth century. Abigail Boucher argues that the concept of class in the long nineteenth century implicitly includes notions of blood, lineage, and bodily 'correctness', and that 'class' was therefore frequently portrayed as an empirical, scientific, and medical certainty. Due to their elevated and highly visual social positions, both historical and fictional aristocrats were frequently pathologized in the public mind and watched for signs of physical excellence or deviance. Using popular fiction, Boucher establishes patterns across decades, genres, and demographics and considers how these patterns react to, normalise, or feed into the advent of new scientific and medical understandings.
Introduction -- Chapter 1: Fashionable Diseases: Consumerism, Class, and Health in the Silver Fork Novels -- Chapter 2: "Unblessed by Offspring": Fertility and the Aristocratic Male in Reynolds's The Mysteries of the Court of London -- Chapter 3: Aristocratic Inbreeding: Exogamy and Endogamy in Sensation Fiction -- Chapter 4: Aristocratic Origins, Heredity, and Evolution in the Fin de Siècle Medieval Revival -- Conclusion.
Keywords: Literature, Modern -- 19th century; Fiction; Medicine and the humanities; Science -- History; Celebrities; Great Britain -- History; Nineteenth-Century Literature; Fiction Literature; Medical Humanities; History of Science; Celebrity Studies; History of Britain and Ireland